Dichlorido-1κCl,3κCl-hexakis[1,1,2,2,3,3(η5)-methylcyclopentadienyl]di-μ2-oxido-1:2κ2O:O;2:3κ2O:O-trihafnium(IV) - Jerzy Pikies; Katarzyna Baranowska; Aleksandra Wisniewska (Acta Crystallographica Section E, 2008)
The title compound, [Hf3(C6H7)6Cl2O2], is a trinuclear molecule having two (MeCp)2HfCl units (MeCp is methylcyclopentadienyl) each connected to an (MeCp)2Hf unit by an oxide bridge. The two Hf—O—Hf bridges are nearly linear. The geometry of the three Hf atoms is tetrahedral (assuming the MeCp group occupies one coordination site); the O—Hf—O angle is 99.8 (5)°. One of the Cl atoms is disordered, with site occupancies of 0.61 (7) and 0.39 (7).